Design of Mathematics Learning Video For Class XI Students of SMA Saraswati I Denpasar - Ni Luh Putu Labasariyani; Ni Luh Putu Mery Marlinda (Logic : Jurnal Rancang Bangun dan Teknologi, 2018)
In accordance with the assessment of KI-3 and KI-4 in the subject of mathematics still have constraints on understanding the concept of student learning so that influence on the learning result. With the existence of these constraints, in this study the researchers combined a scientific approach with video learning. The design used in this study used experimental design of True experimental design that is Posttest Only Control Design. The material given during the course of research action includes the Function Limit, Derivative, and Integral materials. Through the research steps that have been implemented, the final test results are obtained in the experimental class 45% of students belonging to the category that the ability of understanding the concept is very good, and 2.5% of students included in the category of ability to understand the concept is still lacking in the material Limit Function. Then in the Derived material the percentage in very good category is 50% and the enough category is 5%. In Integral material, 50% of students are in very good category and 50% are included in either category. Keywords: Learning Video, Scientific Approach, Experimental Method, Function Limit, Derivative, Integral.